A study on society awarenesss on the impacts of open burning towards the environment / Siti Nurul Asyiqin Mohd Naim and Suzanne Jack Rous - Mohd Naim, Siti Nurul Asyiqin; Jack Rous, Suzanne (2022)
Open burning activity has become a norm among the society due to its easiest method of disposing wastes. The rising environmental issue as a result of open burning activities has become a key concern to the government and society. Therefore, this study was conducted to examine the society awareness on the impacts of open burning towards the environment. The main factors that influence the society awareness studied in this research are policy enforcement, education and normalization. Thus, this study involved a total of 384 respondents from different states in Malaysia had been chosen randomly to answer the questionnaire given. The finding from this research indicates that all the factors examined have significant relationship society awareness.